Partiality and impartiality morality, special relationships, and the wider world - Feltham, Brian; Cottingham, John, 1943- (Oxford : Oxford University Press, 2011)
Issues of impartiality and partiality are a focus of debate in moral theory. Should our personal relationships and commitments have a special place in our moral deliberations? Ten specially written essays by experts in the field offer a variety of perspectives, which will interest readers in both theoretical and practical ethics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Fairness; Perspective (Philosophy)